Explicit Finite Diferences Method for the solution of the acoustic wave equation in a heterogeneous domain - Acasiete Quispe, Frank Henry (2019)
Explicit Finite Diferences Methods (FDM) are used for numerical simulations in seismic problems. In these cases the medium is heterogeneous and for the guarantee of a precise and stable solution there is the need to use refined discretizations for spatial and temporal variables, resulting in large-scale problems. In this paper we present the explicit FDM for the wave equation in a heterogeneous domain and show the results through computer simulations.